A Survey on the Status of Agricultural Cooperatives in Kiyar, Chaharmahal and Bakhtiari Province from the Perspective of Exploiters - pejman rezaee (تعاون و کشاورزی, 2019)
The purpose of this research was to investigate the performance and to understand the effects of the formation of this system on the economic and social characteristics in the Township of Kiyar in Chaharmahal and Bakhtiari province. This study included 28 cooperative companies and 126 operators. The study objective was applied and research method is descriptive – analytical. Single-sample T-test, Chi-square and Pearson correlation. The required information has collected on the basis of documentary methods and field study. results showed fragmentation of agricultural land was one of the most important problems in our case study and all of the 28 agricultural cooperatives companies have divided lands between their beneficiaries (The average area of land was 3 hectares and its distribution was 5 points). Water resources productivity was not favorable for cooperatives, and only 15% of cooperatives used modern irrigation practices. In terms of economic satisfaction, the indicators of employment improvement, land quality, satisfaction with water distribution and land division satisfaction were higher than average (2.5). On the contrary, in terms of optimal use of water resources, satisfaction of incomes and expenses, damages and, responses were less than the average (2.5). In the social context, the performance of cooperatives was relatively appropriate, so that the indicators of land acquisition by qualified individuals, increasing social solidarity, preventing immigration and were higher than the average (2.5) And female employment indicators, financial participation of cooperative members was close to the average. In physical indicators, such as distance from cooperatives to village, co-location locator, access satisfaction and were well-evaluated and responses were higher than the average (2.5). In total, the average of social indicators is 3.2, the average of economic indicators was 2.3 and the average physical indicators were 1.3.